Method for judging whether boron diffusion layer in TBC battery is inverted or not

By designing high-temperature oxidation simulation and boron-doped oxide layer in the TBC cell preparation process, the problem of monitoring whether the boron diffusion layer is reversed into a phosphorus diffusion layer is solved, and the process is accurately judged and optimized, reducing the impact of battery leakage.

CN119730444APending Publication Date: 2025-03-28HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783761.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the preparation of TBC batteries, it is difficult to monitor whether the boron diffusion layer is reversed into a phosphorus diffusion layer. The existing testing methods are complex and costly, and cannot be applied on the production line.

Method used

By designing a series of steps, including high-temperature oxidation simulates the phosphorus diffusion process, removing the oxide layer and BSG layer, testing the boron atom concentration by ECV, and building a boron doped oxide layer close to the properties of the BSG layer, it is precisely determined whether the boron diffusion layer is reversed into a phosphorus diffusion layer.

Benefits of technology

The accurate judgment of whether the boron diffusion layer is reversed into a phosphorus diffusion layer in the TBC battery preparation process is achieved, providing a basis for optimizing the battery preparation process, thereby reducing the impact of battery leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173454790000111
    Figure BDA0005173454790000111
Patent Text Reader

Abstract

The invention relates to the field of solar cells, and discloses a method for judging whether a boron diffusion layer in a TBC cell is inverted or not, which comprises the following steps of: 1.1) polishing a silicon wafer, primarily depositing a tunneling oxide layer / intrinsic polycrystalline silicon layer, diffusing boron, and secondarily depositing the tunneling oxide layer / intrinsic polycrystalline silicon layer; 1.2) high-temperature oxidation; 1.3) removing an oxide layer, performing alkali cleaning, and removing BSG; measuring the boron concentration of the boron diffusion layer; 2.1) polishing the other silicon wafer, and depositing a tunneling oxide layer / intrinsic polycrystalline silicon layer for the first time; 2.2) high-temperature oxidation; 2.3) performing boron doping on the oxide layer; 2.4) secondary deposition of a tunneling oxide layer / intrinsic polycrystalline silicon layer is carried out, and phosphorus diffusion is carried out; 2.5, PSG removal, alkali cleaning and boron-doped oxide layer removal are carried out, the phosphorus concentration of the intrinsic polycrystalline silicon layer is measured, and whether the boron diffusion layer is inverted.According to the method, through ingenious step design, whether the boron diffusion layer is invertedinto the phosphorus diffusion layer after phosphorus diffusion in the TBC preparation technology to be measured is accurately judged, and therefore the technology can be improved according to the result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solar cells, and in particular to a method for judging whether a boron diffusion layer in a TBC cell is inverted into a phosphorus diffusion layer. Background Art

[0002] At present, the general preparation process of conventional TBC batteries is: double-sided polishing of silicon wafers, deposition of tunneling oxide layer + intrinsic polysilicon layer, boron diffusion to form boron diffusion layer and BSG layer, primary laser, wet processing, deposition of tunneling oxide layer + intrinsic polysilicon layer, phosphorus diffusion to form phosphorus diffusion layer and PSG layer, secondary laser, de-plating, wet processing, coating, screen printing, sintering and other processes. The leakage value in the preparation process is an important parameter that determines the final performance of the TBC battery. In addition to the conventional graphic p-region and n-region isolation region structure that will affect the leakage value, during the phosphorus diffusion process, whether the BSG layer on the surface of the boron diffusion layer can effectively block the phosphorus atoms from diffusing into the boron diffusion layer to prevent the boron diffusion layer from being inverted into a phosphorus diffusion layer is also an important factor affecting the leakage value of the TBC battery. However, it is difficult to monitor whether the boron diffusion layer is inverted into a phosphorus diffusion layer during the battery preparation process, and the current methods used to test the semiconductor doping type (such as Hall effect test, XPS test, etc.) are too complicated and the equipment is expensive, and cannot be applied in the production line.

[0003] In view of this, it is necessary to develop a simple, low-cost and highly accurate method to monitor whether the boron diffusion layer is inverted into a phosphorus diffusion layer during the TBC battery manufacturing process, so as to further optimize the battery preparation process and reduce the impact of battery leakage. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for determining whether the boron diffusion layer in a TBC battery is inverted into a phosphorus diffusion layer. The method of the present invention can accurately determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer after phosphorus diffusion in the preparation process of the TBC to be tested through ingenious step design, so that the process can be improved according to the result.

[0005] The specific technical solution of the present invention is: a method for determining whether a boron diffusion layer in a TBC battery is inverted into a phosphorus diffusion layer, which comprises the following steps: first step: 1.1) According to the target TBC battery preparation method (i.e., the process to be tested), the double-sided polishing of the silicon wafer is performed in sequence, the tunneling oxide layer and the intrinsic polysilicon layer are deposited on the back side once, boron is diffused, and the tunneling oxide layer and the intrinsic polysilicon layer are deposited on the back side for the second time.

[0006] The process of 1.1) of the present invention is carried out completely in accordance with the target TBC battery preparation method. After the above-mentioned boron diffusion treatment, the inner layer and the surface layer of the once deposited intrinsic polysilicon layer will be transformed into a boron diffusion layer and a BSG layer respectively.

[0007] 1.2) High temperature oxidation is performed using the same temperature, time, and oxygen flow rate as the phosphorus diffusion in the target TBC battery preparation method (i.e., compared with the phosphorus diffusion process, no phosphorus source is passed).

[0008] In the conventional TBC battery preparation process, after phosphorus diffusion, the inner layer and the surface layer of the secondary deposited intrinsic polysilicon layer will be transformed into a phosphorus diffusion layer and a PSG layer respectively. In order to simulate the effect of high temperature on the initial boron diffusion layer during phosphorus diffusion, the present invention specifically uses the above-mentioned high temperature oxidation process to simulate the phosphorus diffusion process. In the high temperature oxidation process, except that the phosphorus source is not passed, the temperature, time, and oxygen flow rate are consistent with the phosphorus diffusion process.

[0009] 1.3) Remove the oxide layer, alkali cleaning, and BSG layer; ECV test the boron atomic concentration of the boron diffusion layer.

[0010] After high-temperature oxidation, the oxide layer is removed in turn, the secondary deposited tunnel oxide layer and intrinsic polysilicon layer are removed by alkaline cleaning, and the BSG layer is removed to expose the boron diffusion layer for testing its boron atomic concentration.

[0011] Step 2: 2.1) Take another identical silicon wafer, perform double-sided polishing on the wafer in accordance with 1.1), and deposit a tunnel oxide layer and an intrinsic polysilicon layer on the back side at one time.

[0012] 2.2) High temperature oxidation is performed using the same temperature, time, and oxygen flow rate as the boron diffusion in the target TBC battery preparation method (i.e., compared with the boron diffusion process, no boron source is passed).

[0013] In the second step, no boron diffusion is performed, but high-temperature oxidation treatment is used instead. Compared with the conventional boron diffusion process, the temperature, time and oxygen flow rate remain the same except that the boron source is not passed. The oxide layer formed by the high-temperature oxidation covers the surface of the once deposited intrinsic polysilicon layer. Compared with the boron diffusion layer in the first step, the intrinsic polysilicon layer is equivalent to a "blank control layer" because it is not doped with boron atoms; and the oxide layer simulates the BSG layer on the surface of the boron diffusion layer, so that the process to be tested can be simulated as much as possible.

[0014] 2.3) Boron doping of oxide layer.

[0015] The present invention has found through research that the ability of a pure oxide layer (silicon oxide) to block the inward expansion of phosphorus atoms during the phosphorus diffusion process is usually stronger than that of a BSG layer. This is because a pure oxide layer has a denser structure and fewer defects, while the BSG layer contains boron atoms in addition to silicon and oxygen. The introduction of boron atoms will change the chemical composition and microstructure of the material. Boron atoms will occupy some interstitial positions or alternative positions in BSG, which will provide more diffusion paths for phosphorus atoms. In order to further reduce experimental errors, the present invention deliberately adds a boron doping step for the oxide layer, so that the characteristics of this layer are closer to the BSG layer.

[0016] 2.4) According to 1.1), a tunnel oxide layer and an intrinsic polysilicon layer are deposited on the back side in sequence; phosphorus diffusion is performed according to the target TBC battery preparation method.

[0017] The inner layer and the surface layer of the secondarily deposited intrinsic polysilicon layer after phosphorus diffusion are converted into a phosphorus diffusion layer and a PSG layer, respectively.

[0018] 2.5) Remove the PSG layer, perform alkali cleaning, and remove the boron-doped oxide layer; ECV test the phosphorus atom concentration of the intrinsic polysilicon layer in 2.1); compare the boron atom concentration in 1.3) with the phosphorus atom concentration in 2.5) to determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer.

[0019] After phosphorus diffusion, the PSG layer, phosphorus diffusion layer, secondary deposited tunnel oxide layer and boron doped oxide layer are removed in sequence to expose the secondary deposited intrinsic polysilicon layer for testing its phosphorus atomic concentration. According to the test results, the boron atomic concentration measured last time is compared with the phosphorus atomic concentration measured this time to determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer (if the phosphorus atomic concentration is greater than the boron atomic concentration, the boron diffusion layer is inverted into a phosphorus diffusion layer).

[0020] Preferably, in 2.3), the thickness and refractive index of the boron-doped oxide layer formed after the oxide layer is doped with boron are consistent with those of the BSG layer formed after boron diffusion in 1.1).

[0021] More preferably, in 2.3), the refractive index of the boron-doped oxide layer formed after the oxide layer is doped with boron is 1.48 to 1.52 (to 550 nm).

[0022] During the boron doping of the oxide layer, the refractive index of the boron doped oxide layer can be tested by ellipsometer in the early and middle stages to determine its boron doping concentration. The refractive index of the pure oxide layer is 1.45-1.46 at a wavelength of ~550nm, while the refractive index of the BSG layer is usually 1.48-1.52 at a wavelength of ~550nm. Therefore, in the process of boron doping of the oxide layer, the experimental conditions are adjusted by testing with ellipsometer and other related instruments, so that the refractive index of the boron doped oxide layer is consistent with that of the BSG layer formed after conventional boron diffusion, and the thickness of the layer is also consistent with that of the BSG layer.

[0023] Preferably, in 2.3), after the oxide layer is doped with boron, no boron atoms are doped into the bottom intrinsic polysilicon layer.

[0024] Preferably, in 2.3), the oxide layer obtained in 2.2) is doped with boron by LPCVD.

[0025] Preferably, in 2.3), after the oxide layer is doped with boron, the intrinsic polysilicon layer at the bottom thereof is tested by ECV and shows that no boron atoms are doped, and the square resistance and refractive index remain unchanged; further preferably, after the oxide layer is doped with boron, the square resistance of the intrinsic polysilicon layer at the bottom thereof is ≥100kΩ / □, and the refractive index is 3.4~3.6 (~550nm).

[0026] During the research process, the present invention discovered that when the oxide layer is doped with boron by LPCVD, there is a risk that boron atoms will penetrate the oxide layer and enter the intrinsic polysilicon layer at the bottom, thus causing experimental errors. To this end, the present invention uses three monitoring methods during the test process: (1) ECV test: There are no additional doping atoms inside the intrinsic polysilicon layer after being deposited by LPCVD, so the ECV test will not display the concentration of additional doping atoms. If the corresponding ECV test shows the boron atom doping concentration after the oxide layer is doped with boron, it can be concluded that the boron atoms penetrate the oxide layer and enter the intrinsic polysilicon layer, and vice versa; (2) Square resistance test: Since there are no additional doping atoms inside the intrinsic polysilicon layer, the corresponding square resistance value is quite high. In the early stage of testing the intrinsic polysilicon layer, the square resistance value is relatively high. The square resistance value of the silicon layer is ≥100kΩ / □. If the corresponding square resistance test shows a square resistance value <100kΩ / □ after boron oxide doping, it can be concluded that the boron atoms penetrate the oxide layer and enter the intrinsic polysilicon layer, otherwise it is not true; (3) Refractive index test: The refractive index of the intrinsic polysilicon layer deposited by LPCVD is tested by an ellipsometer and is between 3.4 and 3.6 (~550nm). If the corresponding refractive index test shows a refractive index value >3.6 after boron doping the oxide layer, it can be concluded that the boron atoms penetrate the oxide layer and enter the intrinsic polysilicon layer, otherwise it is not true).

[0027] Preferably, in 1.3), a chain machine is used to remove the oxide layer: the concentration of the HF solution in the chain machine is 20 to 80 wt %, and the belt speed is 0.5 to 5 m / min.

[0028] Preferably, in 1.3), the conditions for alkaline cleaning are: KOH solution concentration 1.7-2.2 wt %, temperature 75-85° C. Alkaline cleaning can remove the secondary deposited tunneling oxide layer and intrinsic polysilicon layer.

[0029] Preferably, in 1.3), a chain machine is used to remove the BSG: the concentration of the HF solution in the chain machine is 20 to 80 wt %, and the belt speed is 0.5 to 5 m / min.

[0030] Preferably, in 2.5), a chain machine is used to remove the PSG: the concentration of the HF solution in the chain machine is 20 to 80 wt %, and the belt speed is 0.5 to 5 m / min.

[0031] Preferably, in 2.5), the alkaline cleaning conditions are: KOH solution concentration 1.7-2.2 wt %, temperature 75-85°C.

[0032] Preferably, in 2.5), a chain machine is used to remove the deboronized oxide layer: the concentration of the HF solution in the chain machine is 20 to 80 wt %, and the belt speed is 0.5 to 5 m / min.

[0033] Compared with the prior art, the beneficial effects of the present invention are: (1) The method of the present invention can accurately determine whether the boron diffusion layer of the TBC to be tested is inverted into a phosphorus diffusion layer after phosphorus diffusion in the preparation process of the TBC to be tested through ingenious step design, so that the process can be improved based on the result.

[0034] (2) After the boron diffusion in the second step, the present invention can simulate the internal diffusion environment of phosphorus atoms in the actual phosphorus diffusion process with high fidelity by constructing a boron-doped oxide layer with properties highly similar to those of the BSG layer, and ultimately further improve the accuracy of the judgment result. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the embodiments.

[0036] A method for determining whether a boron diffusion layer in a TBC battery is inverted into a phosphorus diffusion layer comprises the following steps: first step: 1.1) According to the target TBC battery preparation method (i.e., the process to be tested), the double-sided polishing of the silicon wafer is performed in sequence, the tunneling oxide layer and the intrinsic polysilicon layer are deposited on the back side once, boron is diffused, and the tunneling oxide layer and the intrinsic polysilicon layer are deposited on the back side for the second time.

[0037] The process of 1.1) of the present invention is carried out completely in accordance with the target TBC battery preparation method. After the above-mentioned boron diffusion treatment, the inner layer and the surface layer of the once deposited intrinsic polysilicon layer will be transformed into a boron diffusion layer and a BSG layer respectively.

[0038] 1.2) High temperature oxidation is performed using the same temperature, time, and oxygen flow rate as the phosphorus diffusion in the target TBC battery preparation method (i.e., compared with the phosphorus diffusion process, no phosphorus source is passed).

[0039] In the conventional TBC battery preparation process, after phosphorus diffusion, the inner layer and the surface layer of the secondary deposited intrinsic polysilicon layer will be transformed into a phosphorus diffusion layer and a PSG layer respectively. In order to simulate the effect of high temperature on the initial boron diffusion layer during phosphorus diffusion, the present invention specifically uses the above-mentioned high temperature oxidation process to simulate the phosphorus diffusion process. In the high temperature oxidation process, except that the phosphorus source is not passed, the temperature, time, and oxygen flow rate are consistent with the phosphorus diffusion process.

[0040] 1.3) Remove the oxide layer, clean with alkali, remove the BSG layer; ECV test the boron atomic concentration of the boron diffusion layer. After high-temperature oxidation, remove the oxide layer, clean with alkali, and remove the BSG layer in turn to expose the boron diffusion layer, which is convenient for testing its boron atomic concentration.

[0041] In some preferred implementation cases, in 1.3), a chain machine is used to remove the oxide layer: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min.

[0042] In some preferred implementation cases, in 1.3), the conditions for the alkaline cleaning are: KOH solution concentration 1.7-2.2 wt %, temperature 75-85° C. The alkaline cleaning can remove the secondary deposited tunneling oxide layer and the intrinsic polysilicon layer.

[0043] In some preferred implementation cases, in 1.3), a chain machine is used to remove the BSG: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min.

[0044] Step 2: 2.1) Take another identical silicon wafer, perform double-sided polishing on the wafer in accordance with 1.1), and deposit a tunnel oxide layer and an intrinsic polysilicon layer on the back side at one time.

[0045] 2.2) High temperature oxidation is performed using the same temperature, time, and oxygen flow rate as the boron diffusion in the target TBC battery preparation method (i.e., compared with the boron diffusion process, no boron source is passed).

[0046] In the second step, no boron diffusion is performed, but high-temperature oxidation treatment is used instead. Compared with the conventional boron diffusion process, the temperature, time and oxygen flow rate remain the same except that the boron source is not passed. The oxide layer formed by the high-temperature oxidation covers the surface of the once deposited intrinsic polysilicon layer. Compared with the boron diffusion layer in the first step, the intrinsic polysilicon layer is equivalent to a "blank control layer" because it is not doped with boron atoms; and the oxide layer simulates the BSG layer on the surface of the boron diffusion layer, so that the process to be tested can be simulated as much as possible.

[0047] 2.3) Boron doping of the oxide layer. Through research, the present invention has found that the ability of a pure oxide layer (silicon oxide) to block the inward expansion of phosphorus atoms during the phosphorus diffusion process is usually stronger than that of a BSG layer. This is because a pure oxide layer has a denser structure and fewer defects, while the BSG layer contains boron atoms in addition to silicon and oxygen. The introduction of boron atoms will change the chemical composition and microstructure of the material. Boron atoms will occupy some interstitial positions or substitution positions in BSG, which will provide more diffusion paths for phosphorus atoms. In order to further reduce experimental errors, the present invention deliberately adds a step of boron doping of the oxide layer, so that the characteristics of this layer are closer to the BSG layer.

[0048] In some preferred implementation cases, in 2.3), the thickness and refractive index of the boron-doped oxide layer formed after the oxide layer is boron-doped are consistent with the BSG layer formed after the boron diffusion in 1.1). Further preferably, in 2.3), the refractive index of the boron-doped oxide layer formed after the oxide layer is boron-doped = 1.48-1.52 (~550nm). During the period of boron doping of the oxide layer, the refractive index of the boron-doped oxide layer can be tested by an ellipsometer in the early and middle stages to determine its boron doping concentration. The refractive index of the pure oxide layer is 1.45-1.46 at a wavelength of ~550nm, while the refractive index of the BSG layer is generally 1.48-1.52 at a wavelength of ~550nm. Therefore, in the process of boron doping of the oxide layer, the experimental conditions are adjusted by testing with relevant instruments such as an ellipsometer, so that on the one hand, the refractive index of the boron-doped oxide layer is consistent with the BSG layer formed after conventional boron diffusion, and on the other hand, the thickness of the layer is also consistent with the BSG layer.

[0049] In some preferred implementation cases, in 2.3), the oxide layer obtained in 2.2) is doped with boron using LPCVD.

[0050] In some preferred implementation cases, in 2.3), after the oxide layer is doped with boron, no boron atoms are doped into the bottom intrinsic polysilicon layer.

[0051] In some preferred implementation cases, in 2.3), after the oxide layer is doped with boron, the intrinsic polysilicon layer at the bottom thereof is tested by ECV and shows that no boron atoms are doped, and the square resistance and refractive index remain unchanged; further preferably, after the oxide layer is doped with boron, the square resistance of the intrinsic polysilicon layer at the bottom thereof is ≥100kΩ / □, and the refractive index is 3.4~3.6 (~550nm).

[0052] During the research process, the present invention discovered that when the oxide layer is doped with boron by LPCVD, there is a risk that boron atoms will penetrate the oxide layer and enter the intrinsic polysilicon layer at the bottom, thus causing experimental errors. To this end, the present invention uses three monitoring methods during the test process: (1) ECV test: There are no additional doping atoms inside the intrinsic polysilicon layer after being deposited by LPCVD, so the ECV test will not display the concentration of additional doping atoms. If the corresponding ECV test shows the boron atom doping concentration after the oxide layer is doped with boron, it can be concluded that the boron atoms penetrate the oxide layer and enter the intrinsic polysilicon layer, and vice versa; (2) Square resistance test: Since there are no additional doping atoms inside the intrinsic polysilicon layer, the corresponding square resistance value is quite high. In the early stage of testing the intrinsic polysilicon layer, the square resistance value is relatively high. The square resistance value of the silicon layer is ≥100kΩ / □. If the corresponding square resistance test shows a square resistance value <100kΩ / □ after boron oxide doping, it can be concluded that the boron atoms penetrate the oxide layer and enter the intrinsic polysilicon layer, otherwise it is not true; (3) Refractive index test: The refractive index of the intrinsic polysilicon layer deposited by LPCVD is tested by an ellipsometer and is between 3.4 and 3.6 (~550nm). If the corresponding refractive index test shows a refractive index value >3.6 after boron doping the oxide layer, it can be concluded that the boron atoms penetrate the oxide layer and enter the intrinsic polysilicon layer, otherwise it is not true).

[0053] 2.4) According to 1.1), a tunnel oxide layer and an intrinsic polysilicon layer are deposited on the back side in sequence; phosphorus diffusion is performed according to the target TBC battery preparation method.

[0054] The inner layer and the surface layer of the secondarily deposited intrinsic polysilicon layer after phosphorus diffusion are converted into a phosphorus diffusion layer and a PSG layer, respectively.

[0055] 2.5) Remove the PSG layer, perform alkali cleaning, and remove the boron-doped oxide layer; ECV test the phosphorus atom concentration of the intrinsic polysilicon layer in 2.1); compare the boron atom concentration in 1.3) with the phosphorus atom concentration in 2.5) to determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer. After phosphorus diffusion, remove the PSG layer, phosphorus diffusion layer, secondary deposited tunneling oxide layer, and boron-doped oxide layer in sequence to expose the secondary deposited intrinsic polysilicon layer for testing its phosphorus atom concentration. According to the test results, compare the boron atom concentration measured last time with the phosphorus atom concentration measured this time to determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer (if the phosphorus atom concentration is greater than the boron atom concentration, the boron diffusion layer is inverted into a phosphorus diffusion layer).

[0056] In some preferred implementation cases, in 2.5), a chain machine is used to remove the PSG: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min.

[0057] In some preferred implementation cases, in 2.5), the conditions for alkaline cleaning are: KOH solution concentration 1.7-2.2 wt %, temperature 75-85°C.

[0058] In some preferred implementation cases, in 2.5), a chain machine is used to remove the deboron-doped oxide layer: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min.

[0059] Specific Examples and Comparative Examples The preparation method of conventional TBC battery is as follows: S1. Double-sided polishing: Place the N-type single crystal silicon wafer cut by diamond wire into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 minutes. The polishing thickness is 4μm and the thinning amount is 0.42g.

[0060] S2, depositing a tunnel oxide layer and an intrinsic polysilicon layer on the back side at once: the conditions for depositing the tunnel oxide layer are: O2 gas flow rate 40000sccm, temperature 600°C, time 600s, and the thickness of the obtained tunnel oxide layer is about 3nm. The conditions for subsequently depositing the intrinsic polysilicon layer are: SiH4 gas flow rate 920sccm, temperature 550°C, time 3.3h, working pressure 300mTorr, and the thickness of the obtained intrinsic polysilicon layer is about 290nm.

[0061] S3. Boron diffusion: The conditions for boron diffusion are: boron diffusion temperature 850°C, diffusion time 10 min, BCl3 gas flow rate 200 sccm, O2 gas flow rate 1200 sccm, oxidation advancement temperature 950°C, O2 flow rate 7000 sccm, advancement time 30 min, and BSG layer thickness is about 45 nm.

[0062] S4. Laser patterning is used to remove the surface BSG layer in the phosphorus diffusion area and the isolation area. The conditions for laser patterning are: laser wavelength 532nm, frequency 600KHz, marking speed 45000mm / s, power 50W, and processing time 3s.

[0063] S5. Alkali cleaning: The conditions of the alkaline solution are: KOH solution concentration is 2.0 wt %, and the temperature is 75°C.

[0064] S6, secondary deposition of tunnel oxide layer and intrinsic polysilicon layer on the back: The conditions for depositing the tunnel oxide layer are: O2 gas flow rate of 30000sccm, temperature of 600℃, time of 450s, and the grown tunnel SiO x The layer thickness is about 2.5nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer basis, with a SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a time of 1.5 h, a working pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0065] S7. Phosphorus diffusion: The conditions for phosphorus diffusion are: first introduce a mixed gas of POCl3 and O2, the phosphorus diffusion temperature is 790°C, the diffusion time is 15 minutes, POCl3 is carried by nitrogen with a flow rate of 1000sccm, the O2 flow rate is 650sccm, the oxidation advancement temperature is 890°C, the O2 flow rate is 3000sccm, the advancement time is 20 minutes, and the PSG layer thickness is about 39nm.

[0066] S8. Laser secondary patterning to remove the PSG layer on the surface of the boron diffusion area and the isolation area: The conditions for laser patterning are: laser wavelength 532nm, frequency 600KHz, marking speed 45000mm / s, power 25W, and processing time 2.7s.

[0067] S9. De-coating: Use a chain etcher to remove the coating on the front and side of the silicon wafer. The volume ratio of the hydrofluoric acid solution and the nitric acid solution in the acid tank is 1:4 (the concentration of the hydrofluoric acid solution is 49wt%, and the concentration of the nitric acid solution is 69wt%), and the belt speed is 1.3m / min.

[0068] S10, cleaning and texturing: put the silicon wafer after the coating is removed into the alkaline texturing tank for wet cleaning and texturing integrated treatment, wherein the concentration of KOH solution in the texturing tank is 1.7wt%, the temperature is maintained at 82℃, and the time is 7min. Then the subsequent acid (HF / HCl) cleaning tank of the texturing tank can further remove the residual PSG layer and BSG layer of the silicon wafer.

[0069] S11, double-sided coating: ALD deposition method is used to deposit AlO on both sides of the processed silicon wafer x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of about 8nm, and the process temperature is controlled at 250℃. Then, SiN is deposited on both sides of the silicon wafer using a tubular PECVD device. x The film has a thickness of about 82nm and a refractive index of 1.95; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1600mTorr, the power is 12000W, the temperature is 450℃, the SiH4 gas flow rate is 1300sccm, the NH3 gas flow rate is 11000sccm, and the deposition time is 10min.

[0070] S12, screen printing, sintering, light injection, to obtain the finished battery: the coated silicon wafer is screen printed on the back to form a metal contact, then sintered at 770°C to form an Ag-Si ohmic contact, and finally repaired by light injection to obtain the final finished battery.

[0071] Example 1 first step: S1.1. Double-sided polishing of silicon wafers: Place the N-type single crystal silicon wafers cut by diamond wire into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 minutes. The polishing thickness is 4μm and the thinning amount is 0.42g.

[0072] S2.1. Deposit a tunnel oxide layer and an intrinsic polysilicon layer on the back side at once: the conditions for depositing the tunnel oxide layer are: O2 gas flow rate 40000sccm, temperature 600°C, time 600s, and the thickness of the resulting tunnel oxide layer is about 3nm. The conditions for subsequently depositing the intrinsic polysilicon layer are: SiH4 gas flow rate 920sccm, temperature 550°C, time 3.3h, working pressure 300mTorr, and the thickness of the resulting intrinsic polysilicon layer is about 290nm.

[0073] S3.1. The conditions for boron diffusion are: boron diffusion temperature 850°C, diffusion time 10 min, BCl3 gas flow rate 200 sccm, O2 gas flow rate 1200 sccm, oxidation advancement temperature 950°C, O2 flow rate 7000 sccm, advancement time 30 min, and BSG layer thickness of about 45 nm.

[0074] S4.1, secondary deposition of tunnel oxide layer and intrinsic polysilicon layer on the back; the conditions for depositing the tunnel oxide layer are: O2 gas flow rate of 30000sccm, temperature of 600℃, time of 450s, and the grown tunnel SiO x The layer thickness is about 2.5nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer basis, with a SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a time of 1.5 h, a working pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0075] S5.1. The conditions for high-temperature oxidation are: first introduce N2 at a temperature of 790°C for 15 minutes; then introduce O2 for oxidation at a temperature of 890°C for 20 minutes, with an O2 flow rate of 3000 sccm, to generate an oxide layer with a thickness of about 39 nm.

[0076] S6.1. Use a chain machine to remove the oxide layer after high-temperature oxidation, wherein the concentration of the HF solution in the chain machine is 40wt% and the belt speed is 3m / min.

[0077] S7.1. Alkaline cleaning to remove the intrinsic polysilicon layer and the tunnel oxide layer in step S4.1, wherein the conditions of the alkaline solution are: KOH solution concentration is 2.0wt%, and the temperature is 75°C.

[0078] S8.1. Use a chain machine to remove the BSG layer on the surface of the boron diffusion layer, wherein the concentration of the HF solution in the chain machine is 40wt% and the belt speed is 3m / min.

[0079] S9.1. Test the boron atom doping concentration on the surface of the boron diffusion layer by ECV.

[0080] Step 2: S1.2. Double-sided polishing of silicon wafers: Place the N-type single crystal silicon wafers cut by diamond wire into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 minutes. The polishing thickness is 4μm and the thinning amount is 0.42g.

[0081] S2.2, depositing a tunnel oxide layer and an intrinsic polysilicon layer on the back side at once: the conditions for depositing the tunnel oxide layer are: O2 gas flow rate 40000sccm, temperature 600°C, time 600s, and the thickness of the obtained tunnel oxide layer is about 3nm. The conditions for subsequently depositing the intrinsic polysilicon layer are: SiH4 gas flow rate 920sccm, temperature 550°C, time 3.3h, working pressure 300mTorr, and the thickness of the obtained intrinsic polysilicon layer is about 290nm.

[0082] S3.2, high temperature oxidation: first introduce N2 at a temperature of 850°C for 10 min, then oxidize at a temperature of 950°C, an O2 flow rate of 7000 sccm, for 30 min, and the thickness of the oxide layer is about 45 nm.

[0083] S4.2. Boron doping of oxide layer: Boron doping of oxide layer is carried out by LPCVD method, with temperature of 850°C, diffusion time of 3min, BCl3 gas flow rate of 20sccm, O2 gas flow rate of 250sccm. Through ECV, square resistance, ellipsometer and other testing and monitoring methods, the characteristics of the obtained boron atom-doped oxide layer are almost the same as those of the BSG layer on the surface of the boron diffusion layer of the conventional TBC battery.

[0084] S5.2, secondary deposition of tunnel oxide layer and intrinsic polysilicon layer on the back; the conditions for depositing the tunnel oxide layer are: O2 gas flow rate of 30000sccm, temperature of 600℃, time of 450s, and the grown tunnel SiO x The layer thickness is about 2.5nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer basis, with a SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a time of 1.5 h, a working pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0085] S6.2. Phosphorus diffusion: The conditions for phosphorus diffusion are as follows: first introduce a mixed gas of POCl3 and O2, the phosphorus diffusion temperature is 790°C, the diffusion time is 15 minutes, POCl3 is carried by nitrogen with a flow rate of 1000sccm, the O2 flow rate is 650sccm, the oxidation advancement temperature is 890°C, the O2 flow rate is 3000sccm, the advancement time is 20 minutes, and the PSG layer thickness is about 39nm.

[0086] S7.2. PSG removal: A chain machine is used to remove the PSG layer on the surface after phosphorus diffusion, wherein the concentration of the HF solution in the chain machine is 40wt% and the belt speed is 3m / min.

[0087] S8.2. Alkali cleaning: Alkali cleaning is performed to remove the phosphorus diffusion layer at the bottom of the PSG layer, wherein the conditions of the alkaline solution are: KOH solution concentration is 2.0 wt %, and the temperature is 75° C.

[0088] S9.2. Removal of boron-doped oxide layer: a chain machine is used to remove the boron-doped oxide layer, wherein the concentration of the HF solution in the chain machine is 40 wt % and the belt speed is 3 m / min.

[0089] S10.2, ECV test surface phosphorus atom doping concentration; S11.2. Compare the phosphorus atom doping concentration in step S10.2 with the boron atom doping concentration in step S9.1 to determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer.

[0090] Comparative Example 1 The only difference from Example 1 is that in the first step, the tunneling oxide layer and the intrinsic polysilicon layer are deposited on the back side again without undergoing a high temperature oxidation step, that is, there is no oxide layer. The specific steps of the first step are as follows: S1.1. Double-sided polishing of silicon wafers: Place the N-type single crystal silicon wafers cut by diamond wire into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 minutes. The polishing thickness is 4μm and the thinning amount is 0.42g.

[0091] S2.1. Deposit a tunnel oxide layer and an intrinsic polysilicon layer on the back side at once: the conditions for depositing the tunnel oxide layer are: O2 gas flow rate 40000sccm, temperature 600°C, time 600s, and the thickness of the resulting tunnel oxide layer is about 3nm. The conditions for subsequently depositing the intrinsic polysilicon layer are: SiH4 gas flow rate 920sccm, temperature 550°C, time 3.3h, working pressure 300mTorr, and the thickness of the resulting intrinsic polysilicon layer is about 290nm.

[0092] S3.1. The conditions for boron diffusion are: boron diffusion temperature 850°C, diffusion time 10 min, BCl3 gas flow rate 200 sccm, O2 gas flow rate 1200 sccm, oxidation advancement temperature 950°C, O2 flow rate 7000 sccm, advancement time 30 min, and BSG layer thickness of about 45 nm.

[0093] S4.1, secondary deposition of tunnel oxide layer and intrinsic polysilicon layer on the back; the conditions for depositing the tunnel oxide layer are: O2 gas flow rate of 30000sccm, temperature of 600℃, time of 450s, and the grown tunnel SiO x The layer thickness is about 2.5nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer basis, with a SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a time of 1.5 h, a working pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0094] S5.1. Alkaline cleaning to remove the intrinsic polysilicon layer and the tunnel oxide layer in step S4.1, wherein the conditions of the alkaline solution are: KOH solution concentration is 2.0wt%, and the temperature is 75°C.

[0095] S6.1. Use a chain machine to remove the BSG layer on the surface of the boron diffusion layer, wherein the concentration of the HF solution in the chain machine is 40wt% and the belt speed is 3m / min.

[0096] S7.1. Test the boron atom doping concentration on the surface of the boron diffusion layer by ECV.

[0097] Comparative Example 2 The only difference from Example 1 is that in the second step, the tunnel oxide layer and the intrinsic polysilicon layer are deposited once and then subjected to high temperature oxidation, but the oxide layer is not doped with boron. The specific steps of the second step are as follows: S1.2. Double-sided polishing of silicon wafers: Place the N-type single crystal silicon wafers cut by diamond wire into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 minutes. The polishing thickness is 4μm and the thinning amount is 0.42g.

[0098] S2.2, depositing a tunnel oxide layer and an intrinsic polysilicon layer on the back side at once: the conditions for depositing the tunnel oxide layer are: O2 gas flow rate 40000sccm, temperature 600°C, time 600s, and the thickness of the obtained tunnel oxide layer is about 3nm. The conditions for subsequently depositing the intrinsic polysilicon layer are: SiH4 gas flow rate 920sccm, temperature 550°C, time 3.3h, working pressure 300mTorr, and the thickness of the obtained intrinsic polysilicon layer is about 290nm.

[0099] S3.2, high temperature oxidation: first introduce N2 at a temperature of 850°C for 10 min, then oxidize at a temperature of 950°C, an O2 flow rate of 7000 sccm, for 30 min, and the thickness of the oxide layer is about 45 nm.

[0100] S4.2, secondary deposition of tunnel oxide layer and intrinsic polysilicon layer on the back; the conditions for depositing the tunnel oxide layer are: O2 gas flow rate of 30000sccm, temperature of 600℃, time of 450s, and the grown tunnel SiO x The layer thickness is about 2.5nm; then tunneling SiO x An i-poly-Si layer is grown again on the layer basis, with a SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a time of 1.5 h, a working pressure of 300 mTorr, and a thickness of the i-poly-Si layer of about 180 nm.

[0101] S5.2. Phosphorus diffusion: The conditions for phosphorus diffusion are as follows: first introduce a mixed gas of POCl3 and O2, the phosphorus diffusion temperature is 790°C, the diffusion time is 15 minutes, POCl3 is carried by nitrogen with a flow rate of 1000sccm, the O2 flow rate is 650sccm, the oxidation advancement temperature is 890°C, the O2 flow rate is 3000sccm, the advancement time is 20 minutes, and the PSG layer thickness is about 39nm.

[0102] S6.2. PSG removal: A chain machine is used to remove the PSG layer on the surface after phosphorus diffusion, wherein the concentration of the HF solution in the chain machine is 40wt% and the belt speed is 3m / min.

[0103] S7.2. Alkali cleaning: Alkali cleaning is performed to remove the phosphorus diffusion layer at the bottom of the PSG layer, wherein the conditions of the alkaline solution are: KOH solution concentration is 2.0 wt %, and the temperature is 75° C.

[0104] S8.2. Removal of boron-doped oxide layer: a chain machine is used to remove the boron-doped oxide layer, wherein the concentration of the HF solution in the chain machine is 40 wt % and the belt speed is 3 m / min.

[0105] S9.2, ECV test surface phosphorus atom doping concentration; S10.2. Compare the phosphorus atom doping concentration in step S9.2 with the boron atom doping concentration in step S9.1 to determine whether the boron diffusion layer is inverted into a phosphorus diffusion layer.

[0106] Test comparison The test results of Example 1 and Comparative Examples 1-2 are shown in Table 1: Table 1 It can be seen from Table 1 that, firstly, in the conventional process steps for preparing TBC batteries, the surface of the boron diffusion layer must be covered with a phosphorus diffusion layer. Therefore, in the high-temperature process of preparing the phosphorus diffusion layer, it is inevitable that the initial boron diffusion layer will be directly affected. Therefore, in Example 1, after the first step of preparing the boron diffusion layer, a secondary deposition tunneling oxide layer, an intrinsic polysilicon layer, and a subsequent high-temperature oxidation process (similar to the high-temperature conditions for phosphorus diffusion) are required, which is closer to the boron diffusion properties in the actual TBC battery. The surface doping concentration of the boron diffusion layer is ~3.1E19cm -3 , the junction depth is ~0.45μm. In addition, the BSG layer formed on the surface of the conventional TBC battery during the preparation of the boron diffusion layer is often used to block the phosphorus atoms from entering the boron diffusion layer during the subsequent phosphorus diffusion process, and the blocking ability of the BSG layer is different from that of the pure oxide layer. Therefore, in the second step of Example 1, the pure oxide layer is doped with boron so that the properties of the doped oxide layer are close to those of the BSG layer, and its refractive index is ~1.497.

[0107] For Comparative Example 1, since the tunnel oxide layer and the intrinsic polysilicon layer were deposited in the first step without undergoing a high temperature oxidation process (similar to the high temperature conditions for phosphorus diffusion), the concentration of doped atoms on the surface of the boron diffusion was high, 3.3E19 cm -3 The junction depth is relatively shallow ~0.42μm, which has obvious errors compared with the actual TBC battery preparation process, affecting the subsequent result judgment.

[0108] For Comparative Example 2, since the pure oxide layer was not doped with boron atoms in the second step, its corresponding oxide layer refractive index of ~1.453 is lower than that of the oxide layer doped with boron atoms. Its ability to block phosphorus atoms in the subsequent phosphorus diffusion process is significantly different from that of the conventional BSG layer, which also affects the subsequent result judgment.

[0109] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0110] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for determining whether a boron diffusion layer in a TBC battery is inverted, characterized in that: 1.1) Polish the silicon wafer according to the process to be tested, deposit the tunnel oxide layer / intrinsic polysilicon layer once, diffuse boron, and deposit the tunnel oxide layer / intrinsic polysilicon layer twice; 1.2) Oxidation is performed using the phosphorus diffusion temperature, time, and oxygen flow rate of the process to be tested; 1.3) Remove the oxide layer, clean with alkali, remove BSG; measure the boron concentration of the boron diffusion layer; 2.1) Polish another silicon wafer according to 1.1) and deposit a tunnel oxide layer / intrinsic polysilicon layer at one time; 2.2) Oxidation is performed using the boron diffusion temperature, time, and oxygen flow rate of the process to be tested; 2.3) Boron doping of oxide layer; 2.4) Deposit tunnel oxide layer / intrinsic polysilicon layer again according to 1.1); diffuse phosphorus according to the process to be tested; 2.5) Remove PSG, perform alkali cleaning, and remove the boron-doped oxide layer; measure the phosphorus concentration of the intrinsic polysilicon layer in 2.1).

2. The method according to claim 1, characterized in that: In 2.3), the thickness and refractive index of the boron-doped oxide layer formed after boron doping of the oxide layer are consistent with those of the BSG layer formed after boron diffusion in 1.1).

3. The method according to claim 2, characterized in that: 2.3), the refractive index of the boron-doped oxide layer formed after the oxide layer is doped with boron is 1.48~1.

52.

4. The method according to claim 1, characterized in that: 2.3), after the oxide layer is doped with boron, no boron atoms are doped into the bottom intrinsic polysilicon layer.

5. The method according to claim 1, characterized in that: In 2.3), the oxide layer obtained in 2.2) is doped with boron by LPCVD.

6. The method according to claim 1, characterized in that: 2.3), after the oxide layer is doped with boron, the intrinsic polysilicon layer at the bottom thereof is tested by ECV and shows that no boron atoms are doped, and the square resistance and refractive index remain unchanged.

7. The method according to claim 6, characterized in that: 2.3), after the oxide layer is doped with boron, the sheet resistance of the intrinsic polysilicon layer at the bottom thereof is ≥100 kΩ / □, and the refractive index is 3.4-3.

6.

8. The method according to claim 1, characterized in that: 1.3) In The oxide layer is removed by a chain machine: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min; The alkaline cleaning conditions are: KOH solution concentration 1.7-2.2 wt%, temperature 75-85°C; The BSG is removed by a chain machine: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min.

9. The method according to claim 1, characterized in that: 2.5) In The PSG is removed by a chain machine: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min; The alkaline cleaning conditions are: KOH solution concentration 1.7-2.2 wt%, temperature 75-85°C; The deboronized oxide layer is removed by a chain machine: the concentration of the HF solution in the chain machine is 20-80 wt %, and the belt speed is 0.5-5 m / min.